UPAYA PEMBERDAYAAN MASYARAKAT MELALUI USAHA KERAJINANTANGAN KAIN SMOK (STUDI KASUS PADA PUSAT KEGIATAN BELAJAR MASYARAKAT (PKBM) EMPOWEING PEMUDA HARAPAN BANGSA KOTA KUPANG) - Rame, Pannu; Makleat, Nirwaning; Selly, Frans Kristian (Universitas Nusa Cendana, 2024)
The aim of this research is to determine community empowerment efforts through the smok cloth handicraft business at PKBM Empowering Pemuda Harapan Bangsa, Kupang City. The smok cloth handicraft group has been established since 2015 until now. The empowerment efforts studied in this research are through awareness, capacity building and empowerment. The type of research used is qualitative with a case study approach. The research location is at PKBM Empowering Pemuda Harapan Bangsa, Kupang City. The subjects of this research were companions, leaders and group members. Data collection techniques use observation, interviews and documentation techniques. Data analysis techniques include data collection, data reduction, data presentation and drawing conclusions. The triangulation used to explain the validity of the data is source triangulation and technique triangulation. The results of the research show that the empowerment efforts carried out through smok cloth handicrafts at PKBM Empowering Pemuda Harapan Bangsa, Kupang City have gone quite well. In the awareness stage, learning residents are given motivation through outreach activities. At the capacity building stage, students are also given training and demonstrations. In the final stage, the empowerment stage, even though the students are still not completely independent, the profits obtained from smok cloth handicrafts so far can be used to meet the daily needs of the students.